1983
DOI: 10.2170/jjphysiol.33.85
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of spontaneous electrical activity in early embryonic heart monitored optically with a potential-sensitive dye.

Abstract: The effects of temperature on spontaneous action potential activity in the 7-9 somite embryonic precontractile chick hearts were investigated using an optical method for monitoring membrane potential. A potential-sensitive merocyanine-rhodanine dye was used as an optical probe.Cooling caused a marked decrease in the frequency of occurrence of the spontaneous action potential.This slowing was associated with a decreased rate of diastolic depolarization of the pacemaker action potential.When the temperature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Excitations which originate in the pace-making area spread over the entire region of the embryonic heart. We have already found, in the 8-somite embryonic precontractile chick heart, 'switching phenomena'; the site exhibiting pace-making priority was first situated in the right pre-atrium, and then switched over to the left pre-atrium, or vice versa (Sakai, Hirota, Fujii & Kamino, 1983b). Similar phenomena also were often observed in the embryonic rat heart.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Excitations which originate in the pace-making area spread over the entire region of the embryonic heart. We have already found, in the 8-somite embryonic precontractile chick heart, 'switching phenomena'; the site exhibiting pace-making priority was first situated in the right pre-atrium, and then switched over to the left pre-atrium, or vice versa (Sakai, Hirota, Fujii & Kamino, 1983b). Similar phenomena also were often observed in the embryonic rat heart.…”
Section: Resultssupporting
confidence: 68%
“…Thus, our present findings strongly suggest that conventional ideas concerning the onset of contraction of the embryonic rat heart need to be corrected. Hirota et al 1983b, measured in the 7-9 somite preheating hearts at 368-37-4 'C; * §, Hirota et al 1983a; ¶, Fujii et al 1980;11, Hirota et al 1985. We have indicated earlier (Fujii et al 1981 a) one element of a photodiode array detects signals from many active cells at once in a multicellular tissue (Senseman & Salzberg, 1980). We may thus assume that the observed size of the optical signals is a function of the active membrane area and of the optical signal generated by a unit area of active membrane undergoing an action potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that in the adult frog atrial preparation stained with a merocyanine-rhodanine dye (NK 2761) the time course and shape of the absorption change are very similar to the action potential recorded using a microelectrode, under conditions where contraction was reduced in a Ca2+-free bathing solution, and that absorption change accurately reflects phases 0, 1, 2, 3 and 4 in an action potential (Appendix in Hirota et al 1983). Similar results were obtained from the experiments on 5-and 8-day-old embryonic chick hearts (Fujii, Hirota & Kamino, 1980.…”
Section: Discussionmentioning
confidence: 86%
“…The procedures for thermoregulation were as described previously [8]. The temperature of the bathing solution in the chamber was controlled by means of a thermoregulator fixed to the stage of the microscope used for the optical measurements.…”
Section: Thermoregulationmentioning
confidence: 99%